Implementación de un sistema de seguridad y salud en el trabajo en la asociación de producción de vinos de mortiño el Ultimo Inca. - Yanchaguaño Aimacaña, Evelyn Yahaira (2023)
The research purpose project is design a safety and health system at work at mortiño wine production association "EL ULTIMO INCA", this system will constitute a very important tool in the company to avoid occupational risks and reduce or eliminate accidents that occur during workday, in such a way that said system will be based on adequate signage implementation in each area of the company, in order to protect workers health and life in the association. Thus, the present research project has a qualitative and quantitative approach that allows to clearly identify activities that are carried out during wine production, on the other hand, descriptive and bibliographic method was used, which contributed to the knowledge and development of the proposed topic, for which observation and survey were carried out to the Association workers, who gave relevant data on safety and health, in order to improve activities and increase labor efficiency.